Comparison of panoramic radiography and cone beam CT in the assessment of juxta-apical radiolucency - Nascimento, Eduarda Helena Leandro (Dentomaxillofac Radiol, 2018)
OBJECTIVES: To compare the performance of panoramic radiography (PAN) and cone beam CT (CBCT) in the detection of juxta-apical radiolucency (JAR), as well as to investigate, in CBCT images, if there are factors associated with the detection of JAR on PAN. METHODS: Two oral radiologists assessed the presence of JAR in PAN and CBCT images of 175 individuals (308 mandibular third molars). The cortical plates involvement and the JAR size and location were assessed on CBCT to evaluate if these factors were related to JAR detection on PAN. McNemar’s test and multiple logistic regression were performed. RESULTS: PAN and CBCT differed significantly in the detection of JAR (p = 0.001). On PAN, JAR was identified on 24% of the patients while on CBCT its detection increased to 32.6%. JAR was detected only on CBCT and only on PAN in 26 and 7 cases, respectively. Distal/mesial surfaces of dental roots were where JAR was mostly located (84.5%), cortical thinning was found in 59.2% of cases and the mean (SD) of JAR size was 5.03 (±1.8) mm. However, these factors were not associated with JAR detection on PAN (p > 0.05). On the other hand, the location of the cortical involvement (if buccal or lingual) was associated with JAR detection on PAN, which was more detectable when the thinning was on buccal cortical. CONCLUSIONS: Juxta-apical radiolucency is more often detected on CBCT than on PAN. JAR detection on PAN was improved when it was related to the buccal cortical plate of the mandible.